POLITENESS STRATEGIES USED BY THE CHARACTERS IN FINDING NEVERLAND MOVIE (2004) - Sari, Karina; Sili, Surya; Setyowati, Ririn (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2017)
ABSTRACT Politeness is one of important thing in doing conversation to avoid misunderstanding between speaker and hearer during the conversation to make the social interaction running more harmony. The purposes of this research were to find out types of politeness strategies, factors influencing the characters in using politeness strategies and the dominant politeness strategy used by the characters in Finding Neverland movie. The research method in this research was descriptive qualitative research, the theory of politeness strategies by Brown and Levinson (1987) was used to analyze the four types of politeness strategy. The result of this research showed that there were fifty eight utterances represented four politeness strategies used by the characters in Finding Neverland movie. Fourteen utterances represented of bald on record strategy, twenty seven utterances represented of positive politeness strategy, sixteen utterances represented of negative politeness strategy and oneutterance represented bald off record strategy. There are 2 factors influencing the choice of politeness strategies used by the characters in Finding Neverland movie. They are intrinsic payoff and relevant circumstances. Fifty eight utterances categorized as politeness strategies, twenty seven of them belong to positive politeness strategy, so that positive politeness strategy is the most dominantly used by the characters in Finding Neverland movie. Keywords: pragmatics, context, politeness strategies, movie  ABSTRAK Kesantunan merupakan satu hal penting dalam melakukan suatu percakapan untuk menghindari kesalahpaham antara pembicara dan pendengar dalam melakukan percakapan agar interaksi sosial berjalan lebih harmonis. Tujuan dari penelitian ini adalah untuk mengetahui tipe - tipe strategy kesantunan, factor - faktor yang mempengaruhi karakter dalam menggunakan strategi kesantunan dan juga strategi kesantunan yang paling dominan digunakan oleh karakter dalam film Finding Neverland. Metode penelitian ini adalah bersifat deskripsi kualiatif dengan menggunakan teori strategi kesantunan oleh Brown dan Levinson (1987) yang digunakan untuk menganalisa tipe strategi kesantunan. Hasil dari penelitian ini menunjukkan bahwa terdapat lima puluh delapan ujaran yang mewakili keempat strategi kesantunan yang digunakan oleh karakter dalam film Finding Neverland. Empat belas ujaran mewakili strategi kesantunan langsung (tanpa basa basi), dua puluh tujuh ujaran mewakili strategi kesantunan positif, enam belas ujaran mewakili strategi kesantunan negatif, dan satu ujaran mewakili strategi kesantunan tak langsung (basa basi). Terdapat dua faktor yang mempengaruhi pemilihan strategi kesantunan yang digunakan oleh karakter dalam film Finding Neverland. Faktor tersebut adalah faktor payoff dan faktor keadaan. Lima puluh delapan ucapan yang dikategorikan kedalam strategi kesantunan, dua puluh tujuh diantaranya merupakan startegi kesantunan positif, oleh karena itu strategi kesantunan positif adalah strategi yang paling dominan digunakan oleh karakter dalam film Finding Neverland. Kata Kunci: pragmatik, konteks, strategi kesantunan, film